Design and Evaluation of Passive Shoulder Joint Tracking Module for Upper-Limb Rehabilitation Robots - Lee, Kyoung-Soub; Park, Jeong-Ho; Beom, Jaewon; Park, Hyung-Soon (Frontiers in Neurorobotics, 2018)
As the number of people suffering from shoulder movement disabilities increases, the demand for shoulder rehabilitation grows. Natural motion of the shoulder joint (Glenohumeral (GH) joint) includes not only three-degrees-of-freedom (DOF) rotation but also three-DOF translation of the joint center due to simultaneous motion of the shoulder girdle. If the motion of the shoulder girdle is restricted, the arm cannot be raised above a certain posture. This paper presents a passive shoulder joint tracking device that allows the three-DOF translation of the shoulder joint while compensating for gravity. The single-DOF vertical tracker with a constant-force spring compensates for the gross weight of the user’s arm, the upper limb rehabilitation device, and the tracker itself while allowing vertical tracking motion. The two-DOF horizontal tracker consists of two linear guides arranged perpendicular to each other. The tracker freely follows the shoulder joint in the horizontal plane. The effect of using the passive shoulder joint tracking device was evaluated via experiments by combining two popular commercial upper limb rehabilitation apparatuses with the proposed tracker. Nineteen subjects (8 healthy persons and 11 patients with shoulder impairments) participated in the evaluation study. The movement of the GH joint and the interactive force between the subject and the commercial rehabilitation device were analyzed while subjects made shoulder movements: flexion/extension, and abduction/adduction. The improved tracker allowed a greater range of motion and reduced interaction. The tracker can be combined with existing commercial rehabilitation devices for more natural shoulder movement during rehabilitation tasks.